2011
DOI: 10.5432/ijshs.201110
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Yo-Yo Intermittent Recovery Tests and Development of Aerobic and Anaerobic Fitness in U-13 and U-17 Soccer Players

Abstract: The study investigated the Yo-Yo intermittent recovery level 1 and level 2 tests (YYIR1 and YYIR2) performed by soccer players at puberty (U-13) and post-puberty (U-17) and related the YYIR1 and YYIR2 results to anaerobic and aerobicˆtness. The subjects were sixteen male pubescent players aged 13.3(0.2) yrs (U-13) andˆfteen male post-pubescent players aged 17.0(0.6) yrs (U-17). The subjects performed YYIR1 and YYIR2 on artiˆcial turf and were also measured for fat-free mass (FFM), Wingate anaerobic test and _V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the computation of YYIR1 test global means, SDs and quantiles (Figure 2), 239 studies or subgroups with a total of 4,726 participants (median of reported age means = 21.1, inter quartile range [IQR] of reported age means = 17.8–24.5 years) were used (Krustrup and Bangsbo, 2001; Krustrup et al, 2003; Mohr et al, 2003, 2010, 2016; Weston et al, 2004; Castagna et al, 2005, 2006b, 2008; Atkins, 2006; Thomas et al, 2006; Rampinini et al, 2007, 2008, 2010; Mujika et al, 2009; Ben Abdelkrim et al, 2010; Chaouachi et al, 2010; Dupont et al, 2010; Veale et al, 2010; Wong et al, 2010; Buchheit et al, 2011; Chtourou et al, 2011; Chuman et al, 2011; Cobley et al, 2011; Markovic and Mikulic, 2011; Matthys et al, 2011; Roberts et al, 2011; Spencer et al, 2011; Ueda et al, 2011; Alemdaroglu et al, 2012; Boullosa et al, 2012, 2013a,b; Cihan et al, 2012; Cone et al, 2012; Deprez et al, 2012, 2014, 2015a,b; Heaney, 2012; Ingebrigtsen et al, 2012, 2014; Lim, 2012; Scanlan et al, 2012, 2014; Shalfawi et al, 2012, 2013; Teplan et al, 2012a,b, 2013; Vernillo et al, 2012; Berdejo-del-Fresno and González-Ravé, 2013; Cullen et al, 2013; Faude et al, 2013; Higham et al, 2013; Idrizovic and Raickovic, 2013; Manzi et al, 2013; Oliveira et al, 2013; Román-Quintana et al, 2013; Wylie et al, 2013; Yuki et al, 2013; Casamichana et al, 2014, 2015; Clarke et al, 2014; Fabregat-Andres et al, 2014; Fanchini et al, 2014, 2015a,b; Hammouda et al, 2014; Hermassi et al, …”
Section: Resultsmentioning
confidence: 99%
“…Computation of YYIR2 test global means, SDs and quantiles (Figure 3) involved 116 studies/subgroups reporting on 2,478 participants (median age = 23.2 years, IQR = 20.7–26.0 years) (Young et al, 2005; De Souza et al, 2006; Krustrup et al, 2006; Thomas et al, 2006; Mohr et al, 2007, 2016; Iaia et al, 2008, 2015, 2017; Morton et al, 2009; Rampinini et al, 2010; Rebelo et al, 2010; Thomassen et al, 2010; Christensen et al, 2011; Chuman et al, 2011; Mooney et al, 2011, 2013a,b; Roberts et al, 2011; Ueda et al, 2011; Gunnarsson et al, 2012; Ingebrigtsen et al, 2012, 2013, 2014; Nakamura et al, 2012; Saunders et al, 2012; Wells et al, 2012, 2014; Bassini et al, 2013; Buchheit et al, 2013; McGawley and Andersson, 2013; Mohr and Krustrup, 2013, 2014, 2016; Owen et al, 2013; Pivovarniček et al, 2013; Yuki et al, 2013; Fanchini et al, 2014; Karavelioglu et al, 2014; Lollo et al, 2014; Miloski et al, 2014; Nunes et al, 2014; Sampaio et al, 2014; Skovgaard et al, 2014; Brocherie et al, 2015a,b; Cholewa et al, 2015; Coelho et al, 2015; Gatterer et al, 2015; Hogarth et al, 2015a,b; Jamurtas et al, 2015; Krustrup and Mohr, 2015; Leme et al, 2015; Mara et al, 2015; Matta et al, 2015; McLean et al, 2015; Michalsik et al, 2015; Mohr, 2015; Rogan, 2015; Stein et al, 2015; Boer and Van Aswegen, 2016; Bouaziz et al, 2016; Chan et al, 2016; Inness et al, 2016; Joo, 2016; Kilit and Arslan, 2016; Lockie et al, 2016a,b,...…”
Section: Resultsmentioning
confidence: 99%
“…Os valores encontrados (1350-1961m) correspondem a um teste feito em dez estágios no Yo-Yo nível 1, o que indicaria a utilização do nível 2 (Bangsbo, 1994), já que os atletas podem ter finalizado a execução do teste não por terem esgotado seu potencial aeróbio, e sim por ter uma fadiga periférica de membros inferiores. Essa indicação fica ainda mais evidente para os valores encontrados no estudo japonês (Chuman et al, 2011). A resistência anaeróbia foi obtida por meio de dois tipos de testes: 7 sprints e RAST, sendo o primeiro relatado em segundos e o segundo em watts, estimados por equações específicas.…”
Section: Discussão Dos Resultadosunclassified
“…A resistência aeróbia foi avaliada por meio de dois testes: Yo-yo (Bangsbo, 1994) e Shuttle-run (Council of Europe, 1988). O Yo-Yo Intermitent Recovery Test nível 1 foi utilizado em três estudos (Chuman, Hoshikawa, Iida, & Nishijima, 2011;Deprez, Vaeyens, Coutts, Lenoir, & Philippaerts, 2012;Kobal et al, 2014) encontrando-se o valor de 1350m para os brasileiros, 2365 ± 251m para os japoneses e para os belgas: 2012 ± 427m (nascidos no 1º trimestre); 1961 ± 416m (2º trimestre); 1900 ± 374m (3º trimestre) e 1770 ± 416m (4º trimestre). O Intermitent Endurance Test nível 2 foi utilizado em um estudo (Matta et al, 2014), encontrando-se 819,5 ± 336,4m.…”
Section: Características Funcionaisunclassified
“…The Yo-Yo tests can discriminate different levels of cross-country skiers. A possible reason for this is exhaustion in both YYIRT1 and YYIRT2 might be reached before maximal activation of the aerobic energy system in moderate trained group having lower anaerobic fitness [17]. In brief, endurance of anaerobic power is emphasized from maximal anaerobic power in cross-country skiers.…”
Section: Open Accessmentioning
confidence: 99%